International drug trafficking structures and socioeconomic drivers of violence in Ecuador - Escobar-Jiménez, Christian (FLACSO - Sede Ecuador, 2024)
This paper seeks a multifactorial explanation to the problem of the increase in violence in Ecuador in recent years. To this end, the topic is presented along two axes. First, it offers a general approach to violence from the transnational and global perspective of organized crime. The general structure of illicit economies is discussed and several explanations for the dynamics of violence are proposed, linking global and local problems. Secondly, data about violence in the country is presented, and the evolution of the different scenarios that arise in each region is discussed. Descriptive statistics are shown, and a model is also proposed, in an exploratory manner, that links different variables of the socioeconomic structure of the country's cantons to relate them to violence. Finally, a review is made of the general situation of prisons in the country.